Impact of Epicatechin on the Oxidation Behavior of Fish Oil during Gastrointestinal Digestion - Yizhuo FAN; Liyan ZHANG; Qiyue YANG; Yehui ZHANG; Wenjuan JIAO (Shipin gongye ke-ji)
O/W fish oil emulsions with varying EPA/DHA ratios (6/1, 5/2, 4/3) were prepared based on an in vitro digestion-oxidation model. The effects of epicatechin (EC) on the changes in lipid hydroperoxides (LPO), thiobarbituric acid reactive substances (TBARS), malondialdehyde (MDA), and 4-hydroxyhexenal (HHE) during digestion were all investigated. The results indicated that the oxidative stability of fish oil emulsions during digestion decreased as the EPA/DHA ratio decreased. LPO, TBARS, MDA and HHE reached the maximum values during small intestine digestion. The formation of LPO, TBARS, MDA and HHE in gastrointestinal digestion was significantly affected by EC concentrations, and the antioxidant effect was increased with the increase of EC concentration. The high concentration of EC group had the best antioxidant effect, while the low concentration of EC group showed the prooxidant phenomenon. The EPA-enhanced fish oil emulsion has good oxidation stability, and the medium and high concentrations of EC have good reducing effects on the formation of oxidation products, which is conducive to improving the oxidation stability of fish oil during digestion.